Analysis of Compliance in Submitting Accountability Reports of Work Unit Treasurers in Central Sulawesi Province - Khairunnisa; Muhammad Din; Sugianto; Masruddin (LP2M IAIN Palopo, 2026)
Compliance with the submission of Accountability Reports (LPJ) by work unit treasurers is an important indicator in supporting the accountability of state financial management. However, in practice, repeated delays in submitting LPJs are still found. This study aims to analyze the level of compliance in submitting LPJs and identify patterns and causes of delays based on administrative documents. This study uses a descriptive quantitative approach with content analysis techniques on the Office Notes extending the deadline for submitting LPJs by work unit treasurers in Central Sulawesi Province for the period January–June 2025. The unit of analysis for this study is the statement of reasons for delays listed in the Office Notes. Data were analyzed through coding, frequency calculation, and percentage presentation. The results show that delays in submitting LPJs occurred in every month of observation, indicating a suboptimal level of compliance with reporting time. Quantitatively, administrative factors were the most dominant cause of delays at 57.1%, followed by technical factors at 28.6% and operational factors at 14.3%. In addition, a shift in the causes of delays between periods was found, where at the beginning of the budget year delays were dominated by administrative factors, while in subsequent periods they began to be influenced by technical and operational factors. This study confirms that delays in submitting the LPJ are influenced by the interaction between internal administrative capacity and the stability of the reporting support system.